EFFECTIVENESS OF THE OIL TO GAS FUEL CONVERSION PROGRAM FOR FISHERMEN IN PALEMBANG CITY - Shelia, Shelia; Sriati, Sriati; Priyanto, Gatot; Widiastuti, Indah; Fariani, Armina (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2024)
The Oil to Gas Fuel Conversion Program aims to make it easier for fishermen to obtain fuel at affordable prices, hence they can increase their income. Program implementation is declared effective if it runs smoothly and produces the expected results. This research aims to analyze the effectiveness of the program, analyze the income of program recipients and non-program recipients, and analyze the relationship between program effectiveness and income. Interviews using questionnaires were conducted with research subjects, namely 51 members of the Joint Business Group who received the program and 30 members who did not receive the program. Data in the form of attitudes or opinions of program recipient respondents are analyzed based on the achievement of effectiveness scores, income data from two groups of respondents were analyzed based on the difference between two means tests, and the relationship between effectiveness and income was analyzed based on the Spearman rank correlation test. The research results showed that the program's effectiveness was 94.20% (very high). The t-count value of 4.816 is greater than the t-table of 1.994, indicating that there is a significant difference between the income of program recipients and non-program recipients. The relationship between program effectiveness and income is very weak and not significant, with a coefficient value of 0.032. The effectiveness of the program does not directly affect income, but the existence of the program increases fishing efforts and the income of program recipients. Keywords: Conversion; effectiveness; fishermen; gas fuel; Spearman Rank Correlation Test